Pengaruh Penggunaan Wordwall terhadap Hasil Belajar Matematika Konsep Bangun Datar Peserta Didik Kelas II MI - Isna Zahrotunnisa; Muhammad Iqbal Nashrulloh (MASALIQ, 2026)
Mathematics learning at the elementary school level plays an important role in developing logical thinking skills and numeracy competencies. However, based on the results of observations at MI NU Rowolaku Kajen, the use of learning media remains very limited and has not utilized engaging media, resulting in low student interest in learning and affecting learning outcomes, particularly in the material on the concept of plane figures. This study aims to examine the effect of using the Wordwall application on the learning outcomes of second-grade students in the material on the concept of plane figures. This study employed a quantitative experimental approach with a one-group pretest-posttest design. The research subjects consisted of 26 second-grade students. Data were collected through a 10-item essay test and analyzed using the Shapiro–Wilk normality test and the Wilcoxon hypothesis test. The results showed an increase in the average score from 75 on the pretest to 82 on the posttest, indicating a 9% improvement in learning outcomes. The results of the hypothesis test showed a significance value of 0.000 (< 0.05), which means that the alternative hypothesis was accepted and the null hypothesis was rejected. Thus, the use of Wordwall learning media has a significant effect on students’ mathematics learning outcomes in the material on the concept of plane figures. These findings contribute to enriching the literature on the implementation of educational games in the early grades of madrasah while also providing an alternative learning model that teachers can adopt to improve students’ numeracy competence.